UPGRADING SKILL DIFABEL PEREMPUAN MELALUI PROGRAM PEMBERDAYAAN. EFEKTIFKAH UNTUK EKONOMI RUMAH TANGGA? - HARIS, ANDI TENRI ELLYANA; GUNAWAN, MUHAMMAD TAUFAN; JUNIARMITA, ANDI SARTIKA (GANEC SWARA, 2023)
This study aims to determine the effectiveness of empowerment programs to improve the skills of women with disabilities, whether it has an impact on their household economy. The research case study was conducted at the Himpunan Wanita Disabilitas Indonesia (HWDI) Makassar. This research is a qualitative descriptive. The data collection technique is carried out with an in-depth interview where this method will develop questions from a prepared list. The analysis method uses a triangulation technique where this technique will mutually confirm the data obtained from each informant. The goal is that the data obtained becomes valid and objective. The results showed that empowerment in the form of improving skills for women with disabilities is still not effective in helping the household economy. This happened because of the lack of post-activity control in the form of follow-up assistance from the organizers for women with disabilities. As a result, women with disabilities have not been able to maximize their potential and skills to produce products that have economic value in society. So that it does not have a significant impact on the household economy of women with disabilities.